The effect of the Justification on the difference of Islamic Jurists: water used to impose purity as a model - Al-Dalaa’a, Muhammed Abdo; Al-Mahamid, Oqab Khaled Muhammad (Journal of Islamic Sciences, 2021)
This study aimed at explain the opinion of scholars of Islamic jurisprudence on the reasons for which the use of water used for purity is prohibited and the effect of this on the difference of Muslim jurists in the jurisprudence branches These reasons and ills are linked to the purposes of Islamic law, The difference between Muslim jurists in the causes and causes of water used and the jurisprudence that emerged from this difference, One of the most notable findings of this research study was that the reasoning is a defined description of the judgment that includes a legal wisdom disciplined by the purposes of Islamic law. and the agreement of the doctrines of Muslim jurists that the prohibition against the reuse of water used for purity has a legitimate cause and wisdom in Islamic jurisprudence, the difference between Muslim jurists in many jurisprudences on this water is based on reasoning and reason and the nature of this study had to be divided into two parts, the first on the truth of the reasoning among scholars of Islamic jurisprudence and scholars of the purposes of Islamic law. and the second on the explanation of water used in purity and the effect of this reasoning and reason on Muslim jurists.